Educational Activity Licensing Procedure: Administrative and Legal Nature - Bilous-Osin, Tetiana (Problems of legality, 2023)
The relevance of the study of the licensing procedure of educational activity is determined primarily by the need to improve the legislation on higher education within the scope of the Law of Ukraine "On Administrative Procedures". Normative acts regulating the licensing of educational activities are classified depending on the subject of regulation and are distinguished: 1) those regulating the static characteristics of licensing of educational activities; 2) those regulating the dynamic characteristics of educational activity licensing. It is substantiated that the procedure for licensing educational activity is a public procedure related to the exercise of the right to educational activity. The features characteristic of the educational activity licensing procedure as a type of administrative procedure are singled out, namely: it is carried out in the manner determined by the legislation on higher education; concerns public-legal relations regarding the provision of rights, freedoms or legitimate interests of individuals in the field of educational activity; is decided with the participation of an administrative body - an executive body, or rather the Ministry of Education and Science; as a result of the administrative procedure, the license is accepted as an administrative act, etc. It was concluded that according to the classification criteria, the licensing procedure of educational activity is a type of: 1) special partial; 2) law enforcement; 3) non-jurisdictional; 4) external; 5) declaratory administrative procedure. It has been established that a license is a decision of an individual nature, which is taken by an executive body authorized to perform the functions of public administration to resolve a specific case for the acquisition, change, termination or realization of rights and/or obligations in the field of education.